Kobe influencer marketing: Using social media to promote a herbal tea brand - Lui, Patricia (Institutional Knowledge at Singapore Management University, 2021)
In July 2019, Evangeline Leong, co-founder and CEO of Kobe, a Singapore-based start-up providing influencer marketing services, had a challenging task ahead of her.